Age Restrictions on Social Media Access for Teenagers Under 16: an Analysis of Its Urgency from the Perspective of Character Education in the Digital Era - Yen Heppy Rahmi; Muhammad Zadri; Zulfani Sesmiarni; Hidayani Syam (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
Social media among adolescents has a significant impact on behavior, psychological well-being, and character development in the digital age. These developments have given rise to various issues, such as exposure to age-inappropriate content, digital addiction, and a decline in the quality of social interactions; consequently, the Indonesian government has formulated a policy restricting social media access for adolescents under the age of 16 as an effort to protect the younger generation. This study aims to analyze the impact of social media use on adolescents, examine government policies regarding age restrictions on social media access, and assess their urgency from the perspective of Islamic character education in the digital age. This study employs a qualitative approach using a descriptive-analytical research design through library research. Data sources were drawn from scientific literature such as books, indexed journals, and policy documents relevant to the research focus. Data analysis was conducted by examining, classifying, and synthesizing various theories and study findings related to social media, adolescent development, digital policies, and Islamic character education.  The findings indicate that social media use has complex effects on adolescents, both positive and negative, particularly in social, psychological, and behavioral development aspects. Age-restriction policies for social media access are considered highly urgent as a form of preventive protection against digital risks faced by adolescents. From the perspective of Islamic character education, such policies are relevant for supporting the process of internalizing moral values, such as self-control, responsibility, and etiquette in the use of digital technology. Keywords: Social Media, Adolescents, Islamic Character Education, Age Restrictions, Digital Age.